Towards high-throughput in situ structural biology using electron cryotomography - Böhning, J; Bharat, T (Elsevier, 2020)
Electron cryotomography is a rapidly evolving method for imaging macromolecules directly within the native environment of cells and tissues. Combined with sub-tomogram averaging, it allows structural and cell biologists to obtain sub-nanometre resolution structures in situ. However, low throughput in cryo-ET sample preparation and data acquisition, as well as difficulties in target localisation and sub-tomogram averaging image processing, limit its widespread usability. In this review, we discuss new advances in the field that address these throughput and technical problems. We focus on recent efforts made to resolve issues in sample thinning, improvement in data collection speed at the microscope, strategies for localisation of macromolecules using correlated light and electron microscopy and advancements made to improve resolution in sub-tomogram averaging. These advances will considerably decrease the amount of time and effort required for cryo-ET and sub-tomogram averaging, ushering in a new era of structural biology where in situ macromolecular structure determination will be routine.